2023
DOI: 10.4236/psych.2023.141002
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Levels of Self-Efficacy as Predictors of Academic Dishonesty among Higher Education Students in Ghana

Abstract: The study focused on the predictive abilities of personality traits and self-efficacy on academic dishonesty among students. After satisfying ethical protocols, the study surveyed 453 higher education students using an analytical cross-section design. Respondents were exposed to respond to three constructs such as personality traits scale, academic self-efficacy scale, and academic dishonesty scale. The data were quantitatively analyzed using means and standard deviations, frequencies and percentages, and regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 60 publications
3
2
0
1
Order By: Relevance
“…Low scores in conscientiousness were associated with carelessness at work [59], dishonest behavior [62], and lower academic achievement [25], and this is in line with this study as was shown, for example, in higher error rate (objective 3.1.4), low self-control (objective 2.1.1) and lower grade (objective 3.1.9) were associated with lower scores in conscientiousness.…”
Section: Discussionsupporting
confidence: 90%
“…Low scores in conscientiousness were associated with carelessness at work [59], dishonest behavior [62], and lower academic achievement [25], and this is in line with this study as was shown, for example, in higher error rate (objective 3.1.4), low self-control (objective 2.1.1) and lower grade (objective 3.1.9) were associated with lower scores in conscientiousness.…”
Section: Discussionsupporting
confidence: 90%
“…High self-efficacy means the students will be willing to undertake school activities and want to perform creditably in school programmes, activities, and schedules, as exhibited by the notion that they will achieve an academic goal (m = 3.70). The finding is consistent with Eshun et al, [56]. However, De…”
Section: Rq2: What Are the Levels Of Self-efficacy Among Undergraduat...supporting
confidence: 92%
“…Moreover, another factor that predicted academic dishonesty was self-efficacy, which produced the highest predictor of dishonesty when it came to academic integrity (11.2%) accounting for the variance. This result is in harmony with Eshun et al, [56]. But the current finding is a sharp contrast to the studies of Wong and Carducci [60], Mazar, Amir, and Ariely [61], and Baumeister et al, [62], which concluded that lower self-efficacy leads to academic dishonesty in students.…”
Section: Rq3: What Are the Dominant Academically Dishonest Behaviours...supporting
confidence: 82%
“…It is important to avoid helping students engage in dishonest academic practices like plagiarism, cheating, and fabrication (Ventayen, 2023). Academic dishonesty and integrity problems have already been written about (Eshun et al, 2023), but ChatGPT has made them worse (Yeadon et al, et al, 2023). It is said that academic integrity and dishonesty problems do not happen because of something unexpected but because of something that already exists and is used as a conduit to perpetrate the crime (Eshun et al, 2023), and ChatGPT does not seem to be an exception.…”
Section: Is Chatgpt a Threat To Academic Integrity Through Academic W...mentioning
confidence: 99%
“…Academic dishonesty and integrity problems have already been written about (Eshun et al, 2023), but ChatGPT has made them worse (Yeadon et al, et al, 2023). It is said that academic integrity and dishonesty problems do not happen because of something unexpected but because of something that already exists and is used as a conduit to perpetrate the crime (Eshun et al, 2023), and ChatGPT does not seem to be an exception. Several reports have been made on the use of ChatGPT and academic integrity.…”
Section: Is Chatgpt a Threat To Academic Integrity Through Academic W...mentioning
confidence: 99%